Efek konsumsi yoghurt probiotik terhadap kadar low density lipoprotein pada penyandang diabetes mellitus tipe 2 - Yuliani, Kartika; Kertia, Nyoman; Lestari, Lily Arsanti (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background : As one of important markers of cardiovascular complication in patients with type 2 diabetes mellitus, low density lipoprotein (LDL) shall be maintained to be in normal range. Based on previous research, consumption of probiotic yogurt contains Lactobacillus acidophilus and Bifidobacterium animalis subsp. Lactis is presumed can improve LDL in patients with type 2 diabetes mellitus but the scientific evidence is still few.Objectives: To investigate the effect of probiotic yogurt on LDL in patients with type 2 diabetes.Methods: This study was double blinded randomized controlled trial which was conducted on 32 patientss with type 2 diabetes mellitus. Subjects were divided randomly into 2 groups and given 4 weeks intervention. Subjects in control group were given conventional yogurt while subjects in intervention group were given probiotic yogurt contains L. acidophilus LA5 and B. animalis subsp. Lactis Bb12. Food intake data was collected 4 times using 24-hour recall method during intervention period. LDL of subjects was measured before and after intervention.Results: There was no significant difference between LDL before and after intervention in control group (128 – 148.5 mg/dL) and intervention group (130 – 120.5 mg/dL). Meanwhile, LDL after intervention in control group and intervention group were significantly different (p<0.05). LDL between energy and macronutrients intake categories were not significantly different.Conclusion: Probiotic yogurt has a better LDL reduction effect in patients with type 2 diabetes mellitus than conventional yogurt, although the reduction is not significant.